Generation of nanopore structures in yttria-stabilized zirconia by femtosecond pulsed laser irradiation - Yuka Yamamuro; Tomotaka Shimoyama; Jiwang Yan (Journal of Materials Research and Technology, 2023)
Femtosecond pulsed laser irradiation of yttria-stabilized zirconia (YSZ) was performed to investigate the feasibility and fundamental characteristics of nanopore structure fabrication. Numerous nanopores were successfully generated on the YSZ surface with only a single laser pulse shot by controlling laser power near the ablation threshold. The nanopore generation mechanism involves light focusing by the convex shape of a crystal grain and ablation inside the grain. By increasing laser power, the number of nanopores increased. Cross-sectional observation revealed that the depth of nanopores was about 500 nm, and nanopores were generated inside the YSZ grains of the top layer while keeping the grains' shapes unchanged. It was found that higher scanning speed and a small number of scans enabled nanopores fabrication without changing the original surface shape, avoiding the removal of the surface layer. Laser-irradiated surfaces of YSZ were characterized by Raman spectroscopy, and it was found that there was no significant phase change in the specimen after nanopore generation compared with the original YSZ surface, confirming that there was no thermal damage to the bulk material. The surface with nanopores showed an enhancement in surface hydrophilicity. These findings demonstrated the possibility of selectively generating nanopores in the top surface of YSZ for use in functional surfaces without serious thermal damage to the workpiece. It is expected that the nanopore generation will lead to new applications of YSZ.